Pemberian Mulsa Jerami Padi (Oryza sativa) Terhadap Gulma dan Produksi Tanaman Kacang Kedelai (Glycine max (L.) Merr) - Yuwindah Gustanti; - Chairul; Zuhri Syam (Universitas Andalas, 2014)
An experiment of giving mulch of rice straw (Oryza sativa) on weeds and crop production soybeans (Glycine max (L.) Merr) has been carried out at the Laboratory of Plant Ecology, Andalas University, Padang from June to September 2013. The purpose of this study was to determine and define how mulch of rice straw suppress weed growth and increase the production of soybeans. This experiment used a Completely Randomized Design with five treatments and five replications. The result showed that rice straw mulching of 300g/10kg can suppressed the growth of weeds, and rice straw mulching of 500g/10kg could increase soybean production. All treatments showed significantly influence on the increase weight of soybeans product. Keyword: mulch, rice straw, soybean, weeds